JAV lietuviškų knygų autoriai, sudarytojai, vertėjai (iki 1904 m.) - Gargasaitė, Dalia (Knygotyra, 1987)
During 30 years, from 1874 up to 1904 (including), in the USA there were printed more than 720 Lithuanian books, small prints, musical publications, paintings and maps (including and repeated printings). Part of them – (about 380 prints) prepared by USA Lithuanians – editors, priests, doctors, musicians, merchants and by the people of an indefinite and unknown professions. They were abuot 50.